Pandangan dan Karakteristik Warga Bantaran Kali Ciliwung di Kampung Melayu Jatinegara terhadap Banjir Berulang dan Upaya Adaptasinya - Ciek Julyati Hisyam; Rini Krisna Dewi; Mohammad Lutfi; Aulia Putri Al-Amin; Salsabilla Az-Zahra; Muhammad Raihan Aditya Malik (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
Flooding is a persistent problem for residents living along the banks of the Ciliwung River, particularly in area X, Tanah Rendah, Kampung Melayu Village, Jatinegara District, East Jakarta. Although this area is regularly affected by flooding with quite high intensity, most residents still choose to survive and develop various adaptation strategies to deal with these conditions. This study aims to analyze the views and characteristics of residents along the banks of the Ciliwung River regarding recurring flooding and identify the forms of adaptation they have undertaken. The study used a qualitative approach with a case study design. Data were obtained through semi-structured interviews and field observations with three informants selected purposively: a young man, the Deputy Head of the Neighborhood Association (RT), and a housewife who owns a food stall. Data analysis was conducted descriptively and qualitatively using Robert Putnam’s social capital theory as an analytical framework. The results show that residents view flooding as a result of a combination of natural factors and human activities, but the risk has been normalized and is considered part of everyday life. The decision to stay was influenced by economic ties, proximity to livelihoods, access to transportation, and strong family and community ties. Social capital in the form of mutual cooperation, family networks, community institutions, and a multi-level communication-based early warning system were key factors supporting community resilience. Adaptations included raising house floors, adjusting household furniture, and cooperation in post-flood evacuation and recovery activities. Research findings confirm that community resilience is built not only through physical adaptation but also through strong social capital. Therefore, flood mitigation policies need to integrate participatory and community-based approaches to better align with the needs and characteristics of local communities.